2019
DOI: 10.5114/pq.2019.87738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mulligan upper cervical manual traction in the treatment of cervicogenic headache: a randomized controlled trial

Abstract: Introduction. Cervicogenic headache (CGH) is a serious condition manifested by upper cervical facet joints dysfunction. Mulligan upper cervical sustained natural apophyseal glide was noted to be effective in CGH but Mulligan upper cervical manual traction (MUCMT) has not yet been investigated. The purpose of the study was to compare the effect of MUCMT vs. traditional treatment (TT) in patients with CGH. Methods. A randomized controlled prospective parallel single-blind trial was performed. overall, 30 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…This is also in agreement with a study by McMakin [44], who reported that microcurrent combined with manual therapy (chiropractic) reduced pain and increased RoM after the first 20-minute session in patients with persistent chronic MTrPs, and concluded that microcurrent therapy made chiropractic very effective in patients having persistent chronic MTrPs. The same observation was noted when hot packs, transcutaneous electrical nerve stimulation, and deep cervical flexors strengthening exercise were applied with or without Mulligan upper cervical manual traction in cervicogenic headache cases in terms of Ndi and upper cervical rotation RoM [45].…”
Section: Discussionsupporting
confidence: 63%
“…This is also in agreement with a study by McMakin [44], who reported that microcurrent combined with manual therapy (chiropractic) reduced pain and increased RoM after the first 20-minute session in patients with persistent chronic MTrPs, and concluded that microcurrent therapy made chiropractic very effective in patients having persistent chronic MTrPs. The same observation was noted when hot packs, transcutaneous electrical nerve stimulation, and deep cervical flexors strengthening exercise were applied with or without Mulligan upper cervical manual traction in cervicogenic headache cases in terms of Ndi and upper cervical rotation RoM [45].…”
Section: Discussionsupporting
confidence: 63%
“…Em um ensaio clínico randomizado, que buscou explorar os efeitos da tração manual superior de Mulligan® no tratamento de indivíduos com dor de cabeça cervicogênica, trouxe resultados expressivos na melhora na intensidade da cefaleia (KHALIL et al, 2019). Em concordância, Chettri et al (2014) utilizaram a tração cervical superior como terapia manual, identificaram que esta auxiliou no afastamento dos segmentos cervicais, mobilização das articulações, aumento do forame intervertebral e relaxamento dos músculos cervicais.…”
Section: Resultados E Discussõesunclassified
“…Physiotherapy can play an important role in the treatment of patients with chronic cervical pain, as it seeks to minimize pain, recover mobility, and strengthen the muscles, providing an improvement in quality of life [7][8][9][10][11]. For this, resources such as photobiomodulation are applied, with the use of low level laser therapy (LLLT), which is characterized by monochromaticity, collimation, spatial and temporal coherence, producing a non-invasive treatment, painless and capable of providing biomodulatory effects on living organisms [12], with anti-inflammatory, pro-repair and analgesic actions [13,14].…”
Section: Introductionmentioning
confidence: 99%